Finland : Look Who's Talking : Implementing Corporate Diversity and Inclusiveness Practices in Finland - Smale, Adam (Routledge, 2023)
This case highlights the issues surrounding the implementation of a diversity and inclusiveness program in the Finnish subsidiaries of a US multinational. The program was developed at the corporate headquarters in the United States. The case explains from the perspective of a local HR manager, how the organization, Petrocom, went about implementing its “Global Organization” vision that included the roll-out of its new “Global Workforce Diversity Management and Inclusiveness Initiative”. It further reveals the challenges faced by the multinational to implement a corporate-centric approach to diversity management in the local Finnish culture and the approach needed to implement the program. After reading this case, the students will be able to identify the kinds of local contextual factors that can challenge the logic and ease of transfer of corporate HRM practices within the multinational firm, understand how the cultural and institutional features of a country can shape employee attitudes about HRM practices in general, and diversity management in particular, critically assess the effectiveness of different methods to achieve global integration of HRM across the multinational, and the role of key stakeholders.
Keywords: Multinational Corporation; Diversity and Inclusiveness; Foreign Subsidiary; Transfer of HRM Practices; Finland; fi=Henkilöstöjohtaminen|en=Human Resource Management|